SAT0400 Epidemiological Aspects of Neurological Impairment in SjÖgren's Syndrome, Data from the Assess French Cohort. (9th June 2015) - Carvajal Alegria, G.; Guellec, D.; Mariette, X.; Gottenberg, J.E.; Dernis, E.; Dubost, J.J.; Trouvin, A.-P.; Hachulla, E.; Larroche, C.; Le Guern, V.; Cornec, D.; Devauchelle-Pensec, V.; et al.
Abstract : Background: Primary Sjögren syndrome (pSS) is an autoimmune disease which may be associated to several systemic manifestations. Neurological manifestations seem to be frequent but prevalence is inconstant in literature (1). Objectives: To assess neurological involvement prevalence in a national multi-center prospective cohort and to study epidemiological aspects of neurological involvement. Methods: The ASSESS (Assessment of Systemic Signs and Evolution in Sjögren's Syndrome) cohort is a French, multi-centre, prospective cohort, set up in 2006, including 395 pSS patients fulfilling American- European Consensus Criteria (AECG). Demographic and clinical data were compared between patients with and without neurological manifestations, and between patients with peripheral nervous system (PNS) manifestations, central nervous system manifestations (CNS) and no manifestations. Medical records of 26 patients with CNS manifestations and/or cranial nerve involvement were reviewed by both local investigator and our group to confirm or invalidate the association between pSS and the neurological manifestations. Results: Data at inclusion were available for 392 patients. Mean follow-up was 33.8 months. Mean age at inclusion was 58 (±12) years. Mean age at diagnosis was 51 (±12) years. Seventy-four of 392 patients (65 females and 9 males) presented neurological manifestations (18.9%). Sixty-three had PNS manifestations (16%) and 14 had CNS manifestations (3.6%). Most frequent peripheral manifestations were pure sensitive neuropathy (9.2%) and sensory-motor neuropathy (5.3%). Only 2 patients (0.6%) had isolated ganglionopathy. Most frequent central manifestations were cerebral vasculitis (5 patients, 1.3%) and myelitis (4 patients, 1.0%) Patients with neurological involvement had more severe disease according to the ESSDAI scoring system, 8.9 (±6.6) versus 3.9 (±4.8). They had more frequently immunomodulatory/immunosuppressive drugs, 32.4% (24/74) versus 13.8% (44/318) (p=0003). Vasculitis was seen in 21 of 73 patients with neurological manifestations (28.8%) and in 30 of 318 patients without (9.4%) (p<0.0001). During follow up, appearance of new neurological symptoms was seen more frequently in patients with neurological manifestations at inclusion, 30.2% (16/53) versus 7.0% (19/270), than in those without neurological manifestations (p<0.0001). Symptoms improvement was seen in 19/76 patients (25%). Conclusions: The prevalence of neurological manifestations in the ASSESS cohort was about 20% and is comparable to data in the literature. Isolated ganglionopathy, which is frequently considered as the most specific neurological manifestation in pSS, was rare (<1%). Neurological manifestations was associated with more general systemic activity and more frequent use of immunosuppressors. References: Carvajal Alegria G et al. Joint Bone Spine. 2014 Jun 20 Disclosure of Interest: None declared